EDITORIAL PROBLEMS IN PREPARATION FOR PUBLICATION OF THE MONUMENTS OF THE SACRED MONODY OF THE KYIVAN CHURCH - Yasinovskyi, Yurii (Prace Polonistyczne, 2025)
The article centres on research into the liturgical chant of the Kyivan Church in its original monodic form. As a practical aspect of the study, Yasinovskyi and other participants in the project edited and published sacred monodies across various genres and forms, including facsimiles and transcriptions in modern notation. Their methodology and critical apparatus were constantly developed and refined. As a result, they achieved an important goal: they created and published a critical edition of musical texts, opening new avenues for analytical musical research that help examine and understand the true musical essence of the sacred monody of the Eastern Rite.